Heart Transplant and Ventricular Assist: Cardiac Surgery and Heart Failure Perspective - Michael T Cain; Michael S Firstenberg; Joseph C Cleveland (US Cardiology Review)
For nearly 60 years, there have been two surgical treatment options for individuals with severe advanced heart failure: heart transplantation or implantation of a left ventricular assist device. As these fields have advanced in parallel, improvements in surgical technique, device development, and patient selection have improved outcomes for both therapies. Development of a comprehensive approach to the management of the most severe forms of advanced heart failure requires a deep understanding of both heart transplantation and durable ventricular assistance, including recent advancements in both fields. This article will review the substantial progress in the fields of heart transplantation and mechanical left ventricular assistance, including recent changes to organ allocation prioritization and left ventricular assist device evaluation, both of which have dramatically influenced practice in these fields.